Sodium valproate enhances efficacy of NKG2D CAR-T cells against glioblastoma - Liu, Junchen; Dai, Kun; Saliu, Muhammad Auwal; Salisu, Mansur Dabai; Gan, Jiangyu; Afolabi, Lukman Olalekan; Yan, Dehong; Zhang, Guizhong; Liu, Maoxuan; Wan, Xiaochun (Frontiers in Immunology, 2025)
Chimeric antigen receptor T-cell (CAR-T) therapies have shown promise in glioblastoma clinical studies, but responses remain inconsistent due to heterogeneous tumor antigen expression and immune evasion post-treatment. NKG2D CAR-T cells have demonstrated a favorable safety profile in patients with hematologic tumors, and showed robust antitumor efficacy in various xenograft models, including glioblastoma. However, malignant glioma cells evade immunological surveillance by reducing NKG2D ligands expression or cleavage. To enhance the effectiveness of NKG2D CAR-T therapy, we investigated the potential of combining NKG2D CAR-T with approved drugs that cross the blood-brain barrier and augment NKG2D ligands expression in glioma cells. We found that sodium valproate (VPA), an antiepileptic drug, significantly increased surface NKG2D ligands expression on glioblastoma cells at a sublethal concentration. VPA treatment enhanced the susceptibility of glioblastoma cells to NKG2D CAR-T mediated cytotoxicity in both 2D monolayer and 3D tumor spheroid models in vitro. Moreover, VPA-treated glioblastoma cells stimulated CAR-T cells to produce higher levels of inflammatory cytokines (IL-2, IFN-γ, and IL-6). Mechanistically, VPA upregulated NKG2D ligands expression via the PI3K/Akt signaling pathway. Additionally, VPA treatment augmented the antitumor activity of NKG2D CAR-T cells in a glioblastoma xenograft model in vivo. These preclinical results suggest that combining VPA with NKG2D CAR-T therapy represents a promising strategy for improving glioblastoma treatment, warranting further clinical investigation.